Synthesis and solid-state reactions of substituted cyclopentadienyl complexes of rhenium, tungsten and molybdenum - Cheng, Lin (My University, 1997)
About one hundred diagonal and lateral isomers of mono- or di-substituted cyclopentadienyl four-legged piano stool transition metal complexes (n5-C5H3R2)ML4 (R1 = R2 = H, Alkyl; M = Re, W, Mo; L = CO, isonitrite, phosphite, phosphine, B i) were synthesized and fully characterized by elemental analysis, IR and NMR spectroscopy. [Abbreviated Abstract. Open document to view full version]
A thesis Submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Degree of Doctor of Philosophy. Johannesburg, October 1997.